O surgimento da agropecuaria missioneira no Rio Grande do Sul e as derivações gastronomicas - Santos, Vilson Flores dos (2014)
This thesis that has the central theme the emergence of missionary agriculture in Rio Grande do Sul and the gastronomic derivations, aiming to investigate the development of husbandry and agricultural missionary, the gastronomic heritage manifested in production practices and social organization, as well as in food culture that produced and remains in ―gaucho‖ universe, demonstrating how this has being transformed in the historical process. The theoretical framework used to aid in the understanding of this work is based on the Historical-Critical Theory proposed by Professor Demerval Saviani. From this framework, it makes possible an interpretation of the different historical periods experienced in this missionary space and each observe agricultural practices and products consumed throughout the historical process. The methodological approach taken to this research is the dialectical movement, and with the written analysis of the period of ―Sete Povos das Missões‖. Understanding the agricultural missionary from its origin initially pervaded the study of historical analysis where the main theoretical models of agriculture were presented to assist in understanding the relationship of this with gastronomy. The sequence was analyzed forms of cultivation, and culinary variations, provided by agents who cultivated this agricultural space at different times, observing the structures and processes that are consistent or logical by the evidence of the analysis theory of the object of study. Then we aimed to conceptualize the missionary agriculture, not only of literary definitions of farming, but hard data, empirical, leaving aside the imaginary conception of history, to address the dynamic view, objective, ultimately, by the degree of economic development, and their gastronomic and social implications. Finally, was made an approach to agriculture, gastronomy, and cultural events (dance, music, festivals, literature, folklore, art and some food.) that people produce and participate actively where the traditions and costumes come and that are passed down from generation to generation, especially orally. As a result confirms the thesis of gastronomic improvement from the eating habits of the natives. Also confirms the fundamental contribution of the agriculture and husbandry in missionary region. I point also the importance that had and still has the culinary knowledge transmitted by many ethnic groups that inhabited and partly still inhabit the region. In the actual time, this confirms the strong influence of missionary cuisine in various menus as transmission of knowledge that is still alive.